Stress Management and its Application in Problems Solution for Managers’ Professional Burnout at Machine-building Companies in Ukraine - Ivanytska, Svitlana; Ivanytska, Iryna; Galayda, Tatyana; Tenytska, Nataliia (International Journal of Engineering and Technology, 2018)
The article is devoted to the study of using possibilities stress management in preventing and overcoming the consequences of professional burnout the managers at Ukrainian machine-building companies. Methodical proposals on the use of stress management technologies to improve the efficiency of staff activities have been developed. Effective personnel management system of the machine-building company, which takes into account all the motivational and psychological components, contributes to the ability of managers to overcome the problems of professional burnout and develop stress resistance in the process of implementing business processes. The scientists made a significant contribution to the research and development of theoretical and practical aspects in solving personnel professional burnout problems in various fields of activity, as well as the use of stress management for this purpose: H. Boyko, E. Ekienabor, Trufanov. M. Gonchar, T. Casserle, A. Manzoor and others. The inadequacy of working out some aspects of the practical application stress management in the activities at industrial companies requires exploring the possibilities of using various methods to prevent manager’s professional burnout syndrome for business entities in the machine-building industry of Ukraine. The purpose of the study is to formulate methodological recommendations on the use of stress management in solving the problems of manager’s professional burnout at machine-building companies in Ukraine to form an effective motivational system. System development and implementation to prevent and overcome the professional burnout of managers in engineering companies has all the prerequisites to become one of the directions for improving personnel management systems and developing effective mechanisms for labor motivation. The machine building industry of Ukraine can apply the latest developments in the field of HR management based on the proposed methodology. The process of applying stress management is reduced to the consistent implementation of measures to prevent the emergence of the syndrome of occupational burnout. Methodical recommendations for the use of stress management technologies for the management personnel of the machine-building company are proposed. The result of using the proposed methodological recommendations for business entities in the machine-building sphere will be in great demand of efficiency human resources and the strengthening competitive positions of companies.